Histologi dan Histomorfometri Testis dan Epididimis Muncak (Muntiacus muntjak muntjak) pada Periode Ranggah Keras (HISTOLOGY AND HISTOMORPHOMETRY OF THE TESTIS AND EPIDIDYMIS OF MUNTJAC (MUNTIACUS MUNTJAK MUNTJAK) DURING HARD ANTLER PERIOD) - Wahyuni, Sri; Agungpriyono, Srihadi; Agil, Muhammad; Yusuf, Tuty Laswardi (Jurnal Veteriner, 2013)
The objective of this study was to describe the histology and histomorphometry of testis and epididymisof muntjac (Muntiacus muntjak muntjak) during hard antler period. The tissues of the testis and epididymisof an adult male muntjac were processed for histological examination and stained with haematoxylineosine(HE). The parenchyma of muntjac’s testis during hard antler period showed tubuli seminiferi waslined with germinal epithelium: spermatogonia, spermatocyte, spermatid that differentiated intospermatozoa. Sertoli cells were found among the germinal cells. In addition, Leydig cells were foundaround the blood vessel of interstitial tissue along with macrophages. Diameter of the seminiferous tubuleand epithelial thickness were 176,60±7,06 ?m and 50,27±3,62 ?m respectively. The epididymal duct wassubdivided into three segments: caput, corpus and cauda. They were lined predominantly withpseudostratified columnar epithelium which was varied in its thickness. The largest diameter of epididymalduct was found in cauda region (324,26±25,79 ?m), while caput epididymidis had the thickest of epithelialcell (62,21±4,21 ?m) and tended to ce thinner in corpus (49,53±3,01 ?m) and cauda epididymidis(16,30±2,27?m). The density of spermatozoa was observed the most in the lumen of cauda region comparedto caput and corpus epididymidis. In conclusion, the structure of histology and histomorphometry of theseminiferous tubule of testis and epididymal duct of muntjac were similar with small ruminants andother Cervidae during hard antler period.
Keywords: muntjac, testis, epididymis, histology, histomorphometry